Enterprise Resource Planning (ERP) System Implementations and Corporate Misconduct - Heese, Jonas; Pacelli, Joseph (The Accounting Review, 2025)
ABSTRACT This study examines whether enterprise resource planning (ERP) implementations are associated with reductions in corporate misconduct. Specifically, we study the relation between staggered facility-level rollouts of ERP systems and facility-level regulatory violations across a large sample of U.S. firms. Our results indicate that facility-level ERP adoptions are associated with substantial reductions in local violations and penalties. Additional analyses suggest that the effects are more pronounced among facilities incorporating advanced analytics into their systems and among workforces that are less resistant to technology change. Overall, our results suggest that ERP systems generate indirect effects that enhance compliance outcomes across a wide range of violations. JEL Classifications: M40, M41